Enhancing Students’ Self-Confidence through the Mordiscvein Learning Model in Plant Tissue Structure and Function Learning - Muhammad Farhan Barata; Intan Agilliana (Yayasan Darussalam Bengkulu, 2025)
Students’ self-confidence is a crucial affective factor in science learning because it influences their willingness to express ideas, make decisions, participate in discussions, and communicate scientific reasoning. However, preliminary observations in biology learning indicated that students’ self-confidence in the topic of plant tissue structure and function remained low, particularly in relation to belief in their own ability, independence in decision-making, positive self-concept, persistence, and courage to express opinions. This study aimed to examine the effect of the Mordiscvein learning model on students’ self-confidence in learning plant tissue structure and function. A quantitative approach with a quasi-experimental design was employed using a nonequivalent control group design. The participants were 66 eleventh-grade students at SMA Perintis 2 Bandar Lampung, consisting of 34 students in the experimental class taught using the Mordiscvein learning model and 32 students in the control class taught using Discovery Learning. Data were collected using a structured self-confidence questionnaire and analyzed through descriptive statistics, normality and homogeneity tests, an independent sample t-test, and effect size analysis. The results showed that the experimental class achieved a higher mean posttest score (86.50%) and N-Gain score (61.10%) than the control class, which obtained a mean posttest score of 67.25% and an N-Gain score of 39.44%. The independent sample t-test indicated a significant difference between the two groups, with t = 3.561, df = 52.418, and Sig. (2-tailed) = 0.001. The Cohen’s d value of 0.86 further indicated a large effect size. These findings demonstrate that the Mordiscvein learning model significantly improves students’ self-confidence in biology learning. The structured stages of Mordiscvein, including Opening Surprise, hypothesis construction, data publication, fact determination, and conclusion building, provide students with repeated opportunities to communicate, make decisions, collaborate, and express scientific ideas confidently. This study implies that Mordiscvein can be used as an alternative student-centered learning model to strengthen affective engagement and self-confidence in science education.